Combined effects of urbanization and connectivity on iconic coastal fishes. Issue 12 (5th October 2016) - Vargas‐Fonseca, Elena; Olds, Andrew D.; Gilby, Ben L.; Connolly, Rod M.; Schoeman, David S.; Huijbers, Chantal M.; Hyndes, Glenn A.; Schlacher, Thomas A.
Abstract: Aim: Disturbance and connectivity shape the structure and spatial distribution of animal populations in all ecosystems, but the combined effects of these factors are rarely measured in coastal seascapes. We used surf zones of exposed sandy beaches in eastern Australia as a model seascape to test for combined effects of coastal urbanization and seascape connectivity (i.e. spatial links between surf zones, estuaries and rocky headlands) on fish assemblages. Location: Four hundred kilometres of exposed surf beaches along the eastern coastline of Australia. Methods: Fish assemblages were surveyed from surf zones of 14 ocean‐exposed sandy beaches using purpose‐built surf baited remote underwater video stations. Results: The degree of coastal urbanization and connectivity were strongly correlated with the spatial distribution of fish species richness and abundance and were of greater importance to surf fishes than local surf conditions. Urbanization was associated with reductions in the abundance of harvested piscivores and fish species richness. Piscivore abundance and species richness were lowest on highly urbanized coastlines, and adjacent to beaches in wilderness areas where recreational fishing is intense. By contrast, seascape connectivity was correlated with the spatial distribution of omnivore and planktivore abundance. Spatial linkages between surf zones and estuaries were also important to two globally threatened guitarfish that are of international conservation significance. Main conclusions: We show for the first time how vulnerable and iconic fish species in surf zones are affected by the presence of coastal cities and the attributes of seascapes in which these cities are embedded. It is possible that greater connectivity may lessen 'urbanization' impacts for species with broad diets and strong ecological links to other ecosystems – this offers new perspectives in coastal conservation, for fishes and beyond.